Optimization and Combination of Green Building Design in Architectural Design - Li, Yuming (Journal of Theory and Practice of Social Science, 2023)
With the advancement of urbanization in China, environmental pollution and resource and energy consumption are becoming increasingly serious. All sectors of society are beginning to realize the problems faced in developing a "green" economy and environmental protection, reasonably reflecting the design principles and goals of green buildings, and fully implementing the concept of green environmental protection. In order to maintain a good relationship between the construction site and design work, and better achieve the original goals, it is necessary to provide open and environmentally friendly facilities for the construction site, adhere to the concept of sustainable development, seek the internal driving force of change, coordinate design work, make more use of civil engineering, reduce resource and energy consumption, and reduce its adverse impact on the environment.